TEKNIK PURSSED LIPS BREATHING TERHADAP POLA NAPAS PASIEN COMMUNITY ACQUERE PNEUMONIA (CAP) - Yantiana Guru, Yustina; Nona, Mariana (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Community Acquired Pneumonia (CAP) is an acute inflammation of the lung parenchyma. CAP is a disease that occurs frequently and is associated with a high mortality rate, especially in elderly patients and patients. Management of Community Acquired Pneumonia can be done pharmacologically and non-pharmacologically. Non-pharmacological therapy that can be carried out in pneumonia patients with ineffective breathing pattern nursing problems according to SIKI is airway management. One other therapy that can be carried out independently by nurses is Pursed Lip Breathing therapyThe pursed lips breathing technique can help induce a slow breathing pattern, increase oxygen transport, help patients control breathing and also train respiratory muscles, it can also increase the release of carbon dioxide caused by trapped carbon dioxide because the alveoli lose their elasticity, so gas exchange cannot be achieved . carried out optimally and increases dead space in the lungs. The method used is a case study of one CAP patient who was treated in the ICU at RSUD dr. T. C. Hillers Maumere. The results of the case study show that the management of nursing care for CAP patients in reducing shortness of breath, namely providing the pursed lips breathing technique for 3 days, resulted in the first day RR 30x/minute, down to 28x/minute, the second day shortness of breath 28x/minute, down to 22x/minute and third day 20x/minute. This shows that the use of the purses lips breathing technique has an effect on reducing shortness of breath in CAP patients.